Bimodal, Multimodal or Platform – What is a Supply Chain Future Strategy? - Nowicka, Katarzyna (European Journal of Economics and Business Studies, 2017)
This paper examines the idea of supply chain strategy in terms of ICT influence on supply chain business model. The aim is to present the most important technologies – Social, Mobile, Analytics (based on Big Data) and Cloud Computing – as the main enablers for reaching competitive advantages by supply chain strategy. Analysis are based on literature and market studies reviews supported by author’s empirical research results on supply chain manager’s perception on future supply chain development. During the analysis conducted in the paper the definitions of supply chain strategy and supply chain business model was introduced. Further the next phase of supply chain evolution was identified and the base for this new phase – the internet platform based on cloud computing – introduced. This solution, together with the rest SMAC technologies, creates new approach on how flows within supply chains are managed. Due to new potential created by SMAC and ubiquitous uncertainty managers should revise the ability to create multimodal supply chain strategy. That strategy is supported by customised supply chain business models able to meet events in the unpredictable environmental framework. The base for multimodal supply chain strategy development is market segmentation where the differentiator is described by value perceived by particular customer.